2015
DOI: 10.1111/desc.12335
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Match Retrieval: a novel anticipation‐based visual working memory paradigm

Abstract: We tested 8- and 10-month-old infants’ Visual Working Memory (VWM) for object-location bindings — what is where — with a novel paradigm, Delayed Match Retrieval, that measured infants’ anticipatory gaze responses (using a Tobii T120 eye tracker). In an inversion of Delayed-Match-to-Sample tasks and with inspiration from the game Memory, in test trials, three face-down virtual ‘cards’ were presented. Two flipped over sequentially (revealing, e.g., a swirl pattern and then a star), and then flipped back face-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 60 publications
0
52
1
Order By: Relevance
“…Following Kaldy et al (2015), infants were shown a series of animated videos on the screen of an eye-tracker, each consisting of three cards with various pictures on them. The left and right cards always had different pictures on them, while the middle card (the sample) displayed the same picture as one of the other cards.…”
Section: Experiments 1 – Mts and Nmts In An Anticipatory Looking Paradigmmentioning
confidence: 99%
See 4 more Smart Citations
“…Following Kaldy et al (2015), infants were shown a series of animated videos on the screen of an eye-tracker, each consisting of three cards with various pictures on them. The left and right cards always had different pictures on them, while the middle card (the sample) displayed the same picture as one of the other cards.…”
Section: Experiments 1 – Mts and Nmts In An Anticipatory Looking Paradigmmentioning
confidence: 99%
“…First, although separate studies have found that 10-month-old infants can succeed at MTS with 2 pairs of stimuli (Kaldy et al, 2015) and at delayed NMTS generalizing to novel stimuli (Diamond, 2006), these studies used very different paradigms from one another. We tested infants on both MTS and NMTS, allowing us to compare performance on the two rules.…”
Section: Experiments 1 – Mts and Nmts In An Anticipatory Looking Paradigmmentioning
confidence: 99%
See 3 more Smart Citations